Antioxidant and anti-inflammatory properties of cherry extract: Nanosystems-based strategies to improve endothelial function and intestinal absorption - Beconcini, D (2020)
Cherry fruit has a high content in flavonoids. These are important diet components protecting against oxidative stress, inflammation, and endothelial dysfunction, which are all involved in the pathogenesis of atherosclerosis, which is the major cause of cardiovascular diseases (CVD). Since the seasonal availability of fresh fruit is limited, research has been focused on cherry extract (CE), which also possesses a high nutraceutical potential. Many clinical studies have demonstrated the nutraceutical efficacy of fresh cherries, but only a few studies on CE antioxidant and anti-inflammatory activities have been carried out. Here, the results concerning the antioxidant and anti-inflammatory activities of CE are reviewed. These were obtained by an in vitro model based on Human Umbilical Vein Endothelial Cells (HUVEC). To clarify the CE mechanism of action, cells were stressed to induce inflammation and endothelial dysfunction. Considering that antioxidants’ polyphenol compounds are easily degraded in the gastrointestinal tract, recent strategies to reduce the degradation and improve the bioavailability of CE are also presented and discussed. In particular, we report on results obtained with nanoparticles (NP) based on chitosan derivatives (Ch-der), which improved the mucoadhesive properties of the chitosan polymers, as well as their positive charge, to favor high cellular interaction and polyphenols intestinal absorption, compared with a non-mucoadhesive negative surface charged poly(lactic-co-glycolic) acid NP. The advantages and safety of different nanosystems loaded with natural CE or other nutraceuticals are also discussed.